A contemporary and a historical patient with an ectopic meningioma. Issue 4 (4th July 2019) - Verhoeven, Veronique; Vrints, Ina; De Keyser, Jeroen; Menovsky, Tomas; Thiessen, Filip; Tondu, Thierry
Abstract: Introduction: Ectopic meningiomas are rare tumors which can be encountered by all surgical specialties. Patients and methods: We report on two different cases, a contemporary one and a historical one, highlighting the diversity of clinical presentations and prognoses of these lesions. Furthermore epidemiological aspects, clinical features, and diagnostic and therapeutic work-up in patients with an ectopic meningioma are reviewed. Results: Typically, ectopic meningiomas present as gradually expanding lesions, causing a variety of symptoms by their mass effect. Diagnosis is based on histological characteristics, which are similar to those of intracranial meningiomas. Treatment is primarily surgical. Conclusions: The cases we report are at different ends of the clinical and prognostic spectrum. Therapeutic options for different clinical scenarios are discussed.